If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sqrt(2x + 5) + -1sqrt(x + -2) = 3 Reorder the terms: qrst(5 + 2x) + -1sqrt(x + -2) = 3 (5 * qrst + 2x * qrst) + -1sqrt(x + -2) = 3 (5qrst + 2qrstx) + -1sqrt(x + -2) = 3 Reorder the terms: 5qrst + 2qrstx + -1qrst(-2 + x) = 3 5qrst + 2qrstx + (-2 * -1qrst + x * -1qrst) = 3 5qrst + 2qrstx + (2qrst + -1qrstx) = 3 Reorder the terms: 5qrst + 2qrst + 2qrstx + -1qrstx = 3 Combine like terms: 5qrst + 2qrst = 7qrst 7qrst + 2qrstx + -1qrstx = 3 Combine like terms: 2qrstx + -1qrstx = 1qrstx 7qrst + 1qrstx = 3 Solving 7qrst + 1qrstx = 3 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Reorder the terms: -3 + 7qrst + 1qrstx = 3 + -3 Combine like terms: 3 + -3 = 0 -3 + 7qrst + 1qrstx = 0 The solution to this equation could not be determined.
| -8x-16y=32 | | (x^6y^12z^3)^2/3 | | (8y+10)(2.8-0.4)=0 | | f(x)=0.5x^2+2x+c | | 2x^2-x^2+25=0 | | 32y=30x | | 14y+8(2.4-0.3y)=0 | | 1.96=x-97.1/.51 | | 7x^2-16xy+4z^2=0 | | 6y+2=2y-6 | | 3.9=y-1.4 | | (x^2-7x-8)/(x^2-5x-6) | | 6x^3y+15x^2y^3=0 | | (12x-4)/(3x-1) | | (3e+1)(4e-8)=0 | | 4p=7(3p+7) | | (3e+1)(4e-8)=o | | 5+3(2y-1)=2(y-3) | | 5y^6-4y^5+2y^3=0 | | 5t=t/60 | | x^2+x+1=3.64 | | x^2+y^2-3x+8y=20 | | 16t^3-4t=0 | | y=2x+32x+64 | | 4/z | | x-3=3(x-7) | | 2x+32x=-64 | | 6(x-1)=6-1 | | 2x+32x+64=0 | | Y=4x^2+29x+7 | | 6(e+1)+3=2e-7 | | 3y+12=-3x |